Análise do transcriptoma da glândula produtora de veneno de Loxosceles intermedia (aranha marrom): perfil de expressão e identificação de novas toxinas - Gremski, Luiza Helena [UNIFESP] (2010)
Loxosceles genus spiders are responsible for accidents all over the world and have clinical importance in the South of Brazil. The venom of these spiders is made up of several toxins, including proteins, which are responsible for the clinical pattern called loxoscelism. To describe the transcriptional profile of the L. intermedia venom gland, we generated a wide cDNA library, and its transcripts were functionally and structurally analyzed. After initial analyses, 1,843 ESTs produced readable sequences that were grouped into 538 clusters, 281 of which were singletons. Nine hundred eighty-five reads (53% of total ESTs) matched to known proteins. Similarity searches showed that toxinencoding transcripts totalize 43% of the total library and comprise a great number of ESTs. The most frequent toxins were from the LiTx family, which are known for their insecticidal activity. Both phospholipase-D and astacin-like metalloproteases toxins account for approximately 9% of total transcripts. Toxins components such as serine proteases, hyaluronidases and venom allergens were also found but with minor representation. Almost 10% of the ESTs encode for proteins involved in cellular processes. This work also describes the stages for cloning, heterologous expression and purification of a cDNA similar to a protease inhibitor identified in the cDNA library. It is known that proteins belonging to this family have an application potential as antithrombotic drugs, acting as therapeutic agents that influences the activity of coagulation factors. These data provide an important overview of the L. intermedia venom gland expression scenario, revealed significant differences from profiles of other spiders from the Loxosceles genus and describe the production of a novel recombinant toxin.